Medieval swords in Iceland. 13 swords from 1100-1600 - Jóhann Gunnar Malmquist 1992- (2015)
Medieval Icelandic swords have received relatively little attention. The period 1100-1600 is the main focus of this research. Surviving swords from this period along with a variety of other resources were used to try to determine whether the swords preserved can indicate anything about how common swords in Iceland actually were. Many might dismiss this as a result of Icelandic society never needing any weapons. The aim of this thesis is to try to cast some light on the preserved swords provenance while providing some long overdue data and information on the swords from 1100-1600. Íslensk sverð hafa fengið tiltölulega litla athygli. Megináhersan er lögð á tímabiðið frá 1100 til 1600 í þessari rannsókn. Sverð frá þessu tímabili ásamt ýmsum öðrum heimildum voru notuð til að reyna að ákveða og skýra alengi og umfang sverða á Íslandi. Markmiðið er að reyna að gefa skýrari hugmynd um hvar sverðin eru niðurkomin ásmt því að safna saman upplýsingum um þau sverð sem eru varðveitt á Íslandi frá árunum 1100 til 1600.